Self-Concept About Mathematics and Achievement Motivation as Correlates of Academic Achievement of Students at Elementary Level - Fatima, Fozia; Ali, Sabir (JSE, 2023)
A relationship was investigated among the three variables such as self-concept about mathematics, achievement motivation, and academic achievement of learners at elementary-level schools of Sargodha. Two questionnaires were used, while academic achievement was measured in the form of students’ annual results in mathematics. A total of 150 students were taken through a convenient sampling technique.